Human Health Risk Assessment of Heavy Metals in Onion Bulbs Cultivated in Katsina State, North West Nigeria - A.I. Yaradua; A. J. Alhassan; A. Nasir; S. S. Matazu; A. Usman; A. Idi; I. U. Muhammad; S. A. Yaro; R. Nasir (Archives of Current Research International, 2020)
Vegetable fields in Katsina State are increasingly being loaded with heavy metals through various pollution sources such as agricultural activities mining and traffic. Onion bulb samples from the three senatorial zones that constitute to make up Katsina state in the North West of Nigeria were collected and the concentrations of seven heavy metals (Pb, Cd, Cr, Fe, Zn, Mn and Ni) in all the samples were determined by atomic absorption spectrometry. The health risk assessment methods developed by the United States Environmental Protection Agency (US EPA) were employed to explore the potential health hazards of heavy metals in the samples on the children and adult population. The highest mean concentration (mg/kg) was observed for Fe, followed by Pb, Zn and Mn. While Cd has the lowest concentration with the heavy metals Cr and Ni being below detection level (BDL). Overall hazard index (Hi) for the heavy metals were within the safety limit. The overall cancer risk to the adults based on pseudo-total metal concentrations exceeded the target value, mainly contributed by Pb. Mn and Zn were the primary heavy metals posing non-cancer risks while Pb caused the greatest cancer risk. It was concluded that consumption of the onion samples from Katsina State may contribute to the population cancer burden.